El Excentrico, 1976-09-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, CA, 2024)
September 20, 1976 [20 de septiembre de 1976]. Ano 27, No 11. Cover contains an illustration of an indigenous woman. This illustration is part of an advertisement for the La Familia Benefit Dance, which would take place at the Terrace Room on Octiber 9, 1976.